2023
DOI: 10.5194/isprs-archives-xlviii-m-2-2023-1001-2023
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic-Static Method (Dsm) for Structural Displacement Analysis Using the Example of a Wooden Church in Domachowo (Poland)

Abstract: Abstract. Medieval architecture in Poland is not widely represented in the tangible cultural heritage. A preserved structure with traces of medieval architecture is the parish church in Domachowo in southern Greater Poland (Wielkopolska). Due to numerous alterations and modernisations, it is now a complex structure showing clear signs of a damaged original geometry.For this reason, a project was initiated to measure the stability of the structure, especially under the influence of extreme external factors: mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The first approach was discussed in a paper at the FIG Congress in Warsaw [18], indicating that, thanks to the second-degree correction, it is possible to "zero" the readings in a quiet time. It was also found that, for the description of the examined phenomenon of forced vibrations, the absolute values of the indications are not important, but their variability, as a result of the impulse pressure of external forces, is [21]. Taking into account the standard errors in the tachymetric measurement, it was initially assumed that the object at the level of the ceiling does not show unambiguous horizontal displacements relative to the floor.…”
Section: The Problem Of Compliance Of the Inclinometer Indications Wi...mentioning
confidence: 99%
See 2 more Smart Citations
“…The first approach was discussed in a paper at the FIG Congress in Warsaw [18], indicating that, thanks to the second-degree correction, it is possible to "zero" the readings in a quiet time. It was also found that, for the description of the examined phenomenon of forced vibrations, the absolute values of the indications are not important, but their variability, as a result of the impulse pressure of external forces, is [21]. Taking into account the standard errors in the tachymetric measurement, it was initially assumed that the object at the level of the ceiling does not show unambiguous horizontal displacements relative to the floor.…”
Section: The Problem Of Compliance Of the Inclinometer Indications Wi...mentioning
confidence: 99%
“…The first approach was discussed in a paper at the FIG Congress in Warsaw [18], indicating that, thanks to the second-degree correction, it is possible to "zero" the readings in a quiet time. It was also found that, for the description of the examined phenomenon of forced vibrations, the absolute values of the indications are not important, but their variability, as a result of the impulse pressure of external forces, is [21].…”
Section: The Problem Of Compliance Of the Inclinometer Indications Wi...mentioning
confidence: 99%
See 1 more Smart Citation